Exploring Implicit and Explicit Attitudes of Employees’ Authentic Organizational Loyalty - Hong, Ji-Woong; Hong, Ah Jeong; Kim, Sang Rak (Frontiers in Psychology, 2021)
The purpose of this study was to develop the OL-IAT (Organizational Loyalty - Implicit Association Test), an IAT tool that measures implicit attitudes toward organizational loyalty, and to verify its predictive validity. Fifteen respondents were randomly selected from among the employees of Company P. The respondents were then asked open questions about the image they held of the target company, and these responses were compared with those of three people who were employees of Company S. Based on their responses, a list of words was compiled for use on the OL-IAT. Evaluation categories, either like-dislike or positive-negative, were developed for this test based on the approach-avoidance words proposed by Ostafin and Palfai (2006). The OL-IAT was then administered to 127 employees of Company P, and self-reporting measures were also devised to measure explicit attitudes. A survey of whether the implicit attitude toward organizational loyalty was consistent with the explicit attitude showed that there was no significant correlation, and the attitude inconsistency was evident in the responses. When differences in rank were accounted for, organizational loyalty attitudes were consistent at the manager level, and organizational participation attitudes were consistent at the manager and general staff levels. This study will aid in the development of effective measures of organizational loyalty and accelerate interventions to increase it, which in turn will positively impact long-term organizational growth.